Discovering the music of the middle Ages [videorecording] - Wilets, Bernard (Encyclopedia Britannica Educational Corporation [producer], 1982)
Defines the role of music in the people's expression of religious devotion and its use in their celebration of everyday earthly pleasures. Illustrates the principal types of musical compositions that were popular during this period. Introduces the common instrumentation used during the Middle Ages.